Commercializing Sustainable Technologies by Developing Attractive Value Propositions: The Case of Photovoltaic Panels. (June 2020) - Vernay, Anne-Lorène; Sohns, Melanie; Schleich, Joachim; Haggège, Meyer
Despite their promise for tackling environmental problems, sustainable technologies are difficult to move from niche to mass markets. They require firms to develop innovative business models. This article focuses on how firms can develop their value propositions to increase the market attractiveness of sustainable technologies that are economically attractive but are difficult to commercialize. The results are based on an analysis of six German utilities that developed offers for power supply self-sufficiency using photovoltaic technology. The article proposes four generic tactics firms can use to market this technology—simplify, mimic, configure, and engage—and describes and discusses how each of these tactics can help firms deliver and capture value. The study also compares and contrasts how firms combine tactics to increase the attractiveness of their value propositions. The article contributes to the growing literature on business models for sustainability and proposes recommendations to help sustainable innovation overcome customer inertia.